2018
DOI: 10.1097/mat.0000000000000618
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of a Structural Reinforced Small Intestinal Submucosa Vascular Graft for Hemodialysis Access in a Porcine Model

Abstract: Synthetic vascular access for hemodialysis exhibits biological and mechanical material properties mismatch with the native vessels. These limitations prevent infiltration of endothelial cells and decrease grafts long-term patency, particularly in small diameter vessels. We aimed to design a curved structural reinforced small intestinal submucosa (SIS) vascular graft for hemodialysis access and to evaluate in a porcine animal model graft patency by Doppler ultrasonography, tissue remodeling by histology, and va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In addition, this study demonstrated that ultrasound techniques can be used to quantify and monitor highly informative morphological (diameter) and functional (compliance and blood flow velocity) graft parameters in an experimental model in which the natural vessel is replaced with a synthetic one. This overcomes the typical use of the ultrasound Doppler which is limited to test the vessel patency . Furthermore, the noninvasive nature of the ultrasound will allow planning future studies in which the animals’ sacrifice is replaced by a multiple time point analysis, in order to reduce the total number of animals required to reach satisfactory statistical power for the study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this study demonstrated that ultrasound techniques can be used to quantify and monitor highly informative morphological (diameter) and functional (compliance and blood flow velocity) graft parameters in an experimental model in which the natural vessel is replaced with a synthetic one. This overcomes the typical use of the ultrasound Doppler which is limited to test the vessel patency . Furthermore, the noninvasive nature of the ultrasound will allow planning future studies in which the animals’ sacrifice is replaced by a multiple time point analysis, in order to reduce the total number of animals required to reach satisfactory statistical power for the study.…”
Section: Discussionmentioning
confidence: 99%
“…For this study, samples were cut into test pieces for chemical, thermal, mechanical, and microscopy assays or stored in plastic containers for sterilization with ethylene oxide for in vivo testing. Mechanical stability and proper sealing of rolled tubes were previously demonstrated both in vitro and in vivo. ,, …”
Section: Methodsmentioning
confidence: 96%
“…Mechanical stability and proper sealing of rolled tubes were previously demonstrated both in vitro and in vivo. 13,14,19 Conjugation. Once the grafts were formed and completely dried, polyethylene glycol (PEG) was conjugated on the surface and the bulk of the material.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…[121][122][123][124] Planar biaxial devices that test samples from the graft wall with the residual stress relieved by a longitudinal cut have also been used. 125,126 Kink resistance and suture retention can be tested experimentally to limit catastrophic failure due to anastomotic failure or graft occlusion during surgical handling. 122,127 In vitro tests also yield important insights on the hemodynamics underlying vascular graft failure, particularly with the use of benchtop systems to characterize flow in different types of vascular grafts.…”
Section: Experimental Models Of Vascular Graft Performancementioning
confidence: 99%